Modal Verbs of Obligation in Quotations and Political Discourse - Zakalashvili, Lusine; Avagyan, Naira (Armenian Folia Anglistika, 2016)
This article discusses the modal verbs of obligation and their function in quotations and political discourse. The usage of modal verbs in speeches strengthens the impact on people, because they emphasize what people should, must, ought to and have to do. A political speech can enhance a politician’s ratings or even secure a place in the history books. Obligation expressed by modal verbs can be strong and weak. Must is chiefly used to express strong obligation. Should, ought to and had better can be used to express weak obligation. The study of modal verbs of obligation in quotations reveals some peculiarities in terms of gender differences.